al-tanqībāt al-īṭāliyyah fī Tall Barrī / Kaḥat - Bīkūrīlā, Baulū
Paolo (Emilio) Pecorella; The Italian Excavations at Tall Barr? / Ka?at; ersch. 1986?; in Arabic, translated and abridged by Q?sim ?uwair